2022
DOI: 10.24123/jeb.v3i1.4705
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the Behavior Intention to Make Purchases Online On E-Commerce

Abstract: This study aims to determine and analyze the factors that influence behavioral intentions to make purchases online with the object of research e-commerce. The focus of this research are performance expectancy, effort expectancy, social influence, anxiety, personal innovativeness, and behavioral intention to purchase online. Sources of data obtained by distributing online questionnaires. Data were collected through questionnaires distributed to 398 respondents an then analyzed using path analysis and MGA (Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Stress is one of the environmental risk factors that can increase the of hypertension. This is in line with research conducted on the community in the working area of the Biha Pesisir Barat Health Center in 2021, which suggests a significant association between stress and the incidence of hypertension (p-value = 0.000, OR = 3.208) [19]. Research in the community in the working area of the North Ternate Siko Care Health Center in 2018 also stated that there was a significant relationship between stress and the incidence of hypertension (OR = 4.583, 95% CI 1.734-11.901) [20].…”
Section: Risk Analysis Of Stress On the Incidence Of Hypertensionsupporting
confidence: 90%
“…Stress is one of the environmental risk factors that can increase the of hypertension. This is in line with research conducted on the community in the working area of the Biha Pesisir Barat Health Center in 2021, which suggests a significant association between stress and the incidence of hypertension (p-value = 0.000, OR = 3.208) [19]. Research in the community in the working area of the North Ternate Siko Care Health Center in 2018 also stated that there was a significant relationship between stress and the incidence of hypertension (OR = 4.583, 95% CI 1.734-11.901) [20].…”
Section: Risk Analysis Of Stress On the Incidence Of Hypertensionsupporting
confidence: 90%
“…Consumer behavior is influenced by cultural characteristics, language, trust, and social impact (Zimu, 2023). Angelina et al (2022) found that factors such as performance expectancy, effort expectancy, social influence, and behavioral intention to purchase online all had a favorable and substantial impact on the intention to make online purchases.…”
Section: Literature Searchmentioning
confidence: 99%
“…Furthermore, in the e-commerce marketplace, the relationship between social influence and other variables, such as the impact of social influence, is examined on consumers' brand engagement (Ban ˜ares et al, 2022), intention toward using e-commerce (Yobou e, 2022), effect on behavior intention (Angelina et al, 2022) and intention toward using agricultural e-commerce (Zarei, 2022). Thus, the following hypothesis was developed:…”
Section: Social Influence and Customer Engagementmentioning
confidence: 99%